THE ANALYSIS OF SCHIZOPHRENIA SYNDROME IN JOANNE GREENBERG’S “I NEVER PROMISED YOU A ROSE GARDEN” - Fatima, Fatima; Zulfikri, Zulfikri; Rengur, Zul Aini; Mansur, Nurfauziah; Putri, Prisna Aswarita (Datokarama English Education Journal, 2024)
This research aimed to discover the reflection of schizophrenia syndrome in Joanne Greenberg’s I Never Promised You a Rose Garden and the reasons why Joanne Greenberg wrote the novel. The research used a descriptive method. The data were divided into two categories: primary data and secondary data. The primary data consisted of the main information taken from the novel I Never Promised You a Rose Garden. The secondary data included the biography of the author and related literature, such as books and online sources, to support the analysis. The data were collected by reading the novel several times, analyzing its dialogue and themes, noting dialogues related to schizophrenia syndrome, and studying the historical background of the author, Joanne Greenberg. In analyzing the data, the researcher applied a genetic structuralism approach, focusing on both the intrinsic and extrinsic elements of the novel. The results of this analysis showed that Deborah Blau, the main character, suffered from schizophrenia syndrome due to her environment. She experienced hallucinations and delusions, which indicated paranoid schizophrenia. She received treatment through psychotherapy administered by her doctor in a mental hospital. Joanne Greenberg wrote the novel to depict the reality of life for people with mental illness. Additionally, the novel was inspired by her personal experiences, which she transformed into the story.